STUDI KASUS PRODUKTIVITAS DAN BIAYA ANGKUTAN DENGAN TRUK ISUZU DI DUA HAK PENGUSAHAAN HUTAN DI SUMATRA BARAT - Dulsalam Dulsalam; Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
A study on productivity and operating cost of Isuzu TWD 20 (1979 model) trucks has been carried .,out at two forest companies in West Sumatra. The result shows that : 1. The average hauling productivity at PT Ragusa Ltd and PT Pasar Besar is 113 m3 km/hour and 211 m km/hour,respectively.2. The average operating cost at PT Ragusa Ltd and Pasar Besar is respectiuely Rp. 93,-/m3 km and Rp. 57, /m3 km.